Rift Valley Fever Virus: A Zoonotic Vector-Borne Pathogen Affecting Human and Livestock Health: ENY2099/IN1403, 5/2023 - Alomar, Abdullah A.; Campbell, Lindsay P.; Mathias, Derrick K.; Burkett-Cadena , Nathan D. (EDIS, 2023)
This publication summarizes the available information about the distribution, vectors, vertebrate hosts, transmission cycles, epidemiology, and control of Rift Valley fever virus.